Perkembangan Securities Crowdfunding Dalam Mendukung Industri Halal - Padrie Payung Siregar; Muhammad Fhareza Deri; Dini Lestari (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The development of the halal industry is increasing rapidly along with increasing public awareness of the importance of consuming halal products. One of the challenges faced by the halal industry is related to financing. Securities crowdfunding appears as an alternative financing that is lawful and in accordance with sharia principles. The literature study adds the important benefits of crowdfunding securities in supporting the halal industry, such as providing easier financial access for halal business actors, opportunities for investors to participate in the growth of the halal industry, increased transparency and accountability, as well as challenges and risks that must be managed. This literature study also identifies the important role of regulation and compliance with rules in developing securities crowdfunding as an effective instrument in supporting the halal industry. This research will use a literature study approach to analyze the development of crowdfunding securities that support the halal industry. Through this method, it is hoped that it can provide important insights for halal industry players, investors, governments, and related institutions in utilizing the potential of crowdfunding securities to support the growth and development of the halal industry.